Clinical assessment of a squamous cell carcinoma located in the posterior oral cavity - Wahyuning Ratnawidya; Endah Ayu Tri Wulandari; Ening Krisnuhoni; Yuniardini Septorini Wimardhani; Anak Iamaroon (Wolters Kluwer Medknow Publications, 2019)
Background: Any changes in the clinical presentation of the oral mucosa in terms of the color, size, texture, and integrity should be carefully checked. Dentists are responsible for doing a comprehensive oral examination in order to find cancer lesions at the initial stage. The prognosis of an oral squamous cell carcinoma (OSCC) is still determined by the stage of the initial diagnosis. The aim of this report was to describe a posterior tongue OSCC case in a patient who underwent general anesthesia due to the gag reflex in order to obtain a thorough clinical assessment of the primary lesion and a representative biopsy sample. Case Report: A 50-year-old woman with a 4-month history of a sore tongue was referred to the Oral Medicine Clinic of the Cipto Mangunkusumo Hospital. The intraoral examination revealed an ulcer measuring 2 cm × 0.5 cm on the right ventral side of the tongue, facing the area near teeth 46 and 47. There was also a 0.5 cm × 0.5 cm × 0.3 cm white cauliflower-like nodule at the anterior portion of the ulcer. Despite the ulcerative appearance of the lesion, the posterior border of the lesion could not be defined due to its location and the patient's high gag reflex. This patient was referred to the Oral Surgery Department for a further analysis of the clinical lesion and a biopsy. The detailed clinical examination under general anesthesia revealed a much larger lesion measuring 7 cm × 4 cm × 0.3 cm. An incisional biopsy specimen was taken, and the histopathology confirmed the diagnosis of a poorly differentiated OSCC. Conclusion: A thorough clinical examination was needed to assess the oral mucosal lesion in the posterior area of the mouth in order to provide a proper definitive diagnosis.